Dynamics-based force sensor using accelerometers-application of hammer throw training aid - Ohta, K.; Umegaki, K.; Murofushi, K.; Komine, A.; Miyaji, C. (The Engineering of sport 7, Volume 1, 2008)
Dynamics-based force sensor using accelerometers which measures forces and joint torques has been developed. In this study we have applied this method to Hammer throw training aid integrating small sensors, signal processing, short-range wireless transmission, wearable data-logger and biofeedback training System. The purpose of this study was to establish methods for the measuring of rotational movement and the biofeedback training System for hammer throwers. Microelectromechanical Systems accelerometers were chosen as the sensor platform capable of because they are noninvasive miniaturized devices and have wide bandwidth. In this System, a wireless data-logger was developed as a wearable device to replace cables and reduce constraint caused by wearing cables. The transmitted data were given as biofeedback Information over a Speaker through signal processing and voltage to frequency conversion.